2020
DOI: 10.3390/molecules25122859
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Peel as Suitable Source of High-Added Value Bioactives: Tailored Functionalized Meat Products

Abstract: In the last few years, the consumer’s concern with the relationship between health and diet has led to the search of foods with functional properties beyond the nutritional. In this framework, the consumption of pomegranate has increased due to their sensorial attributes and remarkable amounts of bioactive compounds, which generate, at the same time, huge amounts of by-products. A search in the Scopus database for the last 10 years has revealed the rising interest in pomegranate peel (PP), the main residue fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 91 publications
0
49
0
Order By: Relevance
“…Muscle foods (meat and fish), being rich in favourable nutrients, are prone to lipid oxidation, protein decomposition, and microbial contaminations, and spoil rapidly compared to other fresh foods during processing and storage [ 13 , 30 ]. The oxidative changes not only result in accumulation of toxic compounds, but also bring in undesirable changes in the colour, flavour, and texture properties, reducing the acceptability and shelf life of muscle food products [ 4 , 12 , 20 , 37 ].…”
Section: Pomegranate In Muscle Food Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Muscle foods (meat and fish), being rich in favourable nutrients, are prone to lipid oxidation, protein decomposition, and microbial contaminations, and spoil rapidly compared to other fresh foods during processing and storage [ 13 , 30 ]. The oxidative changes not only result in accumulation of toxic compounds, but also bring in undesirable changes in the colour, flavour, and texture properties, reducing the acceptability and shelf life of muscle food products [ 4 , 12 , 20 , 37 ].…”
Section: Pomegranate In Muscle Food Applicationsmentioning
confidence: 99%
“…The oxidative changes not only result in accumulation of toxic compounds, but also bring in undesirable changes in the colour, flavour, and texture properties, reducing the acceptability and shelf life of muscle food products [ 4 , 12 , 20 , 37 ]. In order to inhibit the undesirable changes and maintain the physicochemical quality and safety of products, bioactive components derived from pomegranate wastes, in the form of powder and or extract, have been used as valuable additives in various muscle food products [ 30 ]. Figure 3 also highlights the beneficial effect on quality attributes of muscle foods and associated health benefits of biomolecules derived from pomegranate by-products.…”
Section: Pomegranate In Muscle Food Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the antioxidant properties associated with phenolic extracts derived from different biomass of the Myrtaceae family, several studies also reported their role as antimicrobial agents [ 14 , 37 , 41 ]. This is especially interesting because more and more microorganisms are becoming resistant to available antibiotics; thus, there is an urgent need to search for alternative biomolecules that can inhibit the broad spectrum of multidrug-resistant microorganisms [ 20 , 86 ]. Boulekbache-Makhlouf et al [ 4 ] demonstrated the antimicrobial potential of crude extract from the fruit of E. globulus against three bacteria, namely, Staphylococcus aureus , Bacillus subtilis , and Klebsiella pneumoniae .…”
Section: Biological Activities Of Extracts Obtained From mentioning
confidence: 99%
“…Consequently, in recent years, there has been an increase in the development of eco-friendly and sustainable avant-garde technologies combined with smart solvents to preserve the functionality of the extracted compounds. In the last decade, ultrasound-assisted extraction (UAE), microwave-assisted extraction (MAE), supercritical fluid extraction (SFE), and subcritical water extraction (SWE) were outlined as safe and effective technologies in the field of recovery of biomolecules from forest biomass [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%